A Study on Factors Affecting Children’s Post Divorce Adjustment: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In many people's lives nowadays, divorce is a widespread occurrence. It affects the family's nature and thus shifts the life of the spouses and introduces a number of coping challenges to the children of divorce. This thesis looked at the research on the overall divorce adaptation of adolescents. Review the interaction between different families' and children's transition factors from three points of view (1) stress inebriation, (2) stress outsourcing or (3). Kid comparability checklist, family assessment system and the divorce modification inventory were included in the tools. The family responsibilities, behavior regulation and affective engagement were the most critical influences to promote social and emotional change. Families with more probable after divorce to mitigate childhood maladjustment, shared care, and family traditions are retained. Parental tension and hostility can affect kids registered by social isolation, anxiety and depression.